Calcium-Boron Addition Promotes Pollen Germination and Fruit Set of Mango. Issue 2 (3rd April 2017) - Muengkaew, Ratthaphol; Chaiprasart, Peerasak; Wongsawad, Pheravut
ABSTRACT: Different concentrations of calcium and boron were investigated for their effects on pollen germination and fruit set in mango cv. Mahachanok grown for off-season production. A randomized complete block design utilizing five treatments (1.0, 2.0, 3.0, and 4.0 mL/L 40% calcium (Ca) and 0.3% boron (B) with water as a control) with six replicates per treatment was used. The solution was sprayed onto trees at three stages, i.e., bud swell, floral development (also termed the "asparagus" stage), and before flower opening. Foliar application of Ca-B at a concentration of 3.0 mL/L exerted a significant stimulatory effect on pollen germination and pollen tube growth ( P ≤ 0.05). This concentration also increased inflorescence length and the number of hermaphroditic inflorescences, and enhanced fruit set of mango cv. Mahachanok ( P ≤ 0.05). Foliar application of the Ca-B solution at a concentration of 3.0 mL/L, therefore, generated positive effects with the trees producing more fruit and having greater productivity.